2021
DOI: 10.1177/00375497211003130
|View full text |Cite
|
Sign up to set email alerts
|

A DEVS-based engine for building digital quadruplets

Abstract: Development of Embedded Real-Time Systems is prone to error, and developing bug-free applications is expensive and no guarantees can be provided. We introduce the concept of Digital Quadruplet which includes: a 3D virtual representation of the physical world (a Digital Twin), a Discrete-Event formal model of the system of interest (called the “Digital Triplet”), which can be used for formal analysis as well as simulation studies, and a physical model of the real system under study for experimentation (called t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Niyonkuru and Wainer 125 introduced the concept of Digital Quadruplet to improve the development of Embedded Real-Time Systems: a 3D virtual replica of the real world under study (which is called here the DT), a discrete-event formal model of the system of interest that can be used for formal analysis and simulation studies (called the Triplet), and a physical model of the real system under investigation for experimentation (called Quadruplet).…”
Section: Discussionmentioning
confidence: 99%
“…Niyonkuru and Wainer 125 introduced the concept of Digital Quadruplet to improve the development of Embedded Real-Time Systems: a 3D virtual replica of the real world under study (which is called here the DT), a discrete-event formal model of the system of interest that can be used for formal analysis and simulation studies (called the Triplet), and a physical model of the real system under investigation for experimentation (called Quadruplet).…”
Section: Discussionmentioning
confidence: 99%
“…28 A scaling factor can be provided, transforming hours into minutes, minutes into seconds, etc. This is important when incorporating hardware in the loop to the virtual framework 32 since, for instance, the previous use case handles periods of 30 min, but we may want to perform tests with sensors sending data every minute. In addition, xDEVS can interrupt the real-time simulation with the arrival of data sent by an external hardware device.…”
Section: Use Casesmentioning
confidence: 99%
“…For instance, Lu and Olofsson 35 proposed an integrated framework to support the development of construction simulation models utilizing the advanced capabilities of Building Information Modeling (BIM) systems. A more advanced example is presented in Niyonkuru and Wainer, 36 which introduced an environment that can integrate simulation modeling with BIM visualization capabilities to develop real-time executable simulation models. Pen ˜a-Mora et al 37 suggested the use of hybrid modeling of DES and System Dynamics (SD) to abstract different levels of management in constructions systems.…”
Section: Construction Simulationmentioning
confidence: 99%